NILAI HARMONI DAN KESELAMATAN ALAM SEMESTA - Tjahjadi, Indra (Balai Bahasa Jawa Timur, 2009)
Reaason for Harmony: Anthology of Indonesian Writing in Translation oleh Kadek Krishna Adidharma(ed.). Ubud Writers & Readers Festival. 2008. ix+ 102 halaman